Universal Values as a Meeting Point in Abrahamic Religions: Insights from Schuon and Smith - Jameelah, Mariyam; Aiman, Rahmat (Peradaban Journal of Religion and Society, 2025)
This study examines the concept of universal human values within the Jewish, Christian, and Islamic traditions, exploring their potential to foster global peace and solidarity. Drawing on the profound insights of Frithjof Schuon and Huston Smith, this research highlights the shared core values present across these three distinct religions, despite their differences in form, doctrine, and ritual. These shared values include justice, compassion, respect for human dignity, and responsibility toward others and the environment. Through the lens of the Perennial Philosophy, both thinkers posit that these values are manifestations of a single, underlying Truth common to all religions. Schuon focuses on the transcendental principles underpinning each tradition, emphasizing the metaphysical and esoteric dimensions of these values as reflections of divine truths. For instance, he points to teachings on social justice, respect for human dignity, and responsibility toward nature in Judaism; the emphasis on compassion and solidarity, including the call to love one’s neighbor and even enemies, in Christianity; and the concept of Tawhid, stressing the unity of God and humanity, which underpins teachings on social justice and fair treatment in Islam. Smith, while acknowledging the metaphysical aspects, emphasizes the practical, ethical, and social implications of these values, particularly their role in building a just and harmonious society.